Flexible piezoelectric energy nanogenerator based on ZnO nanotubes hosted in a polycarbonate membrane. (April 2015) - Stassi, Stefano; Cauda, Valentina; Ottone, Carminna; Chiodoni, Angelica; Pirri, Candido Fabrizio; Canavese, Giancarlo
Abstract: Highly oriented zinc oxide (ZnO) nanotubes were synthesized in a porous polycarbonate (PC) matrix, leading to a highly flexible ZnO–PC composite able to work as efficient energy nanogenerator. The crystalline direction of the ZnO c -axis is obtained parallel to the membrane surface, thus advantageous for the exploitation of composite under bending stresses. Three different pore sizes of the templating PC membranes were successfully employed, i.e., having nominal pore diameter 30, 50 and 100 nm, thus obtaining three different ZnO one-dimensional nanostructures supported into the PC membrane. The ZnO–PC nanogenerators were successfully tested both under compressive and bending strains, showing an influence of the ZnO nanotube size on the output voltage. Using the 100 nm pore PC membrane, a maximum output voltage of 1.15 V, a maximum current of 100 μA and a maximum output power density of 287.5 mW/cm 3 were reached, being these values among the highest reached in zinc oxide-based piezoelectric nanogenerators. Such remarkable results make the nanostructured ZnO–PC composite a promising material for energy harvesting applications. Graphical abstract: Highlights: Oriented ZnO nanotubes were templated in porous flexible polycarbonate matrices. The ZnO-PC composites work as efficient energy nanogenerator. The c-axis direction is advantageous to exploit the ZnO-PC under bending stress. The nanostructured composite performed remarkable power density generation. The ZnO-PC composite is sensible to even slight pressures from water drop falls.